Pelaksanaan Program Penanggulangan Kemiskinan Selama Pandemi Covid-19 di Kota Bukittinggi Sumatera Barat - Nabilla Nabilla; Roni Ekha Putera; Hendri Koeswara (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2022)
The problem of poverty will not stop to be discussed, the inequality of economic income conditions in society is no longer a trivial problem that can be ignored, because poverty is also a source of factors for other problems in people's lives. The government as an agent of public trust in managing the life of the state also strives to realize the goals of the state in terms of prosperity and welfare of the people, accordance goals of the Indonesian state in the Preamble 1945 Constitution in the fourth paragraph which reads